Ibn Khaldun and Tasawwuf (Sufism): A Different Approach to The Shaykh and Other Relevant Concepts - Küçük, Hülya (İbn Haldun Çalışmaları Dergisi, 2016)
Discussions on whether or not a shaykh is necessary in sulūk (spiritual pathway) have especially intensified in the eighth/fourteenth century, and even after Andalusian scholars had long taken care of this issue, the well-known scholar Abū Isḥāq al-Shātibī (d. 790/1388) compiled a survey-like treatise on this issue by appealing to the erudition of Moroccan scholars. The Moroccan scholars include: Abū Abdullāh Muḥammad b. Ibrāhīm b. ‘Abbād al-Rundī (d. 792/1376) and Abū al-’Abbās Aḥmad b. Qāsim b. ‘Abd al-Raḥmān al-Kabbāb (d. 778/1376). These two scholars gave their fatwā (judicial opinion) in Wansharī’s extant work Al-mi’yār almurīb. Ibn Khaldūn who has seen Shātibī’s Risālah put forward his views on this matter (in spite of not being a scholar of Sufism, and also not being asked of his stance). It was solely for this purpose that he had penned Shifā al-sāil li tahdhīb al-masāil. Ibn Khaldūn speaks of three kinds of Sufism in his book, and treats these three Sufistic characteristic types in relation to whether or not a shaykh is necessary.